ANALISIS PSIKOLOGI SASTRA DALAM CERITA ALTERNATE UNIVERSE “BENDERA SETENGAH TIANG” KARYA @97NISAIURS - Azzahra, Mahesa; Dewi, Trie Utari (Kantor Bahasa Provinsi Maluku, 2024)
Abstract Current technological developments influence the development of digital literature. One popular form of the digital literature among teenagers is Alternate Universe (AU) genre, entitled